EVALUATION THE ANTIOXIDANT ACTIVITY O F SESAME COAT AND SESAME CAKE EXTRACTS - & et al., Shamurad (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
This study was aimed to evaluate the anti-oxidant activity of mmthanol extracts from roasted and unroasted sesame seeds cake (RSC, URSC) and ethanol extracts from sesameccoat (SC) usingDDPPH and reducing power activity (RPA) assay. The quantitative and qualitative analysis of obtained extracts were done using RP-HPLC technique, the results revealed that the extracts were contained anti-oxidents(lignans ) sesamin ,ssesamolin andssesamol in different amounts Also the RPA of URSC extract at (10, 20, & 50 mg/ml) was similar to that ofbBHT , while that for RSC was similar to BHT at 30 mg/ml. Additionally, The RPA SC extract was comparable to that of BHT at ( 20 , 30  , and 50 mg/ml). It has been noticed that the radical scavengingaability (RSA) of BHT was greater than of the experimental samples that evaluated by DPPH assay. Mean time the RSA of the studied extracts was increased with increase of extracts concentrations from 10-50 mg/g. Based on the results of this study, sesame coat, sesame cake (from roasted and unroasted sesame seeds) extracts could be used asppotential natural anti-oxidant topprotectooil-rich food to avoid theppossible risks resulted from using the syntheticaantioxidants to prevent food.